In Silico Study of the Antidiabetic Activity of Secondary Metabolites from Noni Fruit (Morinda citrifolia L.) Against PPARγ Receptors - Surya, Syifanindya Andari; Amarilis, Bunga; Hafidz, Nur Parida Mahdhani; Azzahra, Raden Siti Salma; Abdullah, Astriani (Innovative: Journal Of Social Science Research, 2024)
Diabetes Mellitus is a metabolic disease disorder with the characteristics of an increase in blood glucose. Diabetes mellitus affects 422 million people worldwide. One of the herbal plants in Indonesia that has antidiabetic activity is Noni fruit (Morinda citrifolia L.). This study aims to find new antidiabetic drug candidates in silico inhibiting Peroxisome proliferator-activated receptor gamma (PPARγ) from the Noni fruit plant. The methods used includes Lipinski prediction, ADMETOX prediction, and molecular docking. The low Gibbs free energy are scopoletin with a value of -9.81 kcal/mol and kaempferol with a value of -10.70 kcal/mol proves that those compounds are able to interact well on the (PPARγ) receptor so that they have antidiabetic activity.